Multi laser beams directed energy deposition of a high-strength and high-toughness TC11 titanium alloy with coaxial wire feeding - J.Q. Yao; Y.S. Wang; X.W. Liu; X.F. Chen; S.M. Chen; L. Hu; H.T. Liu; Y.H. Qian; Y. Cheng; B. Song; C.Z. Yan; Y.S. Shi (Next Materials)
Wire-feed laser directed energy deposition (WLDED) additive manufacturing technology, which utilizes a wire alloy, offers a high material utilization rate and produces less pollution, making it ideal for efficiently processing large components. However, the conventional paraxial wire feeding method faces challenges, such as inadequate coupling between the laser and the wire, as well as limited flexibility of the processing head when creating complex parts. This study introduces a new multi-laser beam coaxial wire feeding device designed to fabricate and analyze the high-strength and high-toughness TC11 titanium alloy, frequently used in critical load-bearing aerospace components. By optimizing process parameters like wire feeding speed (WFS) and travel speed (TS), formability was improved with WFS set at 500 mm/min and TS at 4 mm/s. The findings show that the microstructural changes in various regions and the mechanical properties in the typical direction can be significantly influenced by the use of coaxial WLDED with specific thermal gradient (G) and solidification rate (R) characteristics, along with particular laser-wire coupling positions. The combined effects of a lower thermal gradient and heterogeneous nucleation, resulting from coaxial wire feeding, are essential in refining the microstructure of materials used in coaxial WLDED. As a result, the fundamental mechanisms underlying microstructural evolution and the improvement of tensile properties through multi-laser beam WLDED with a coaxial processing head have been elucidated.